Identificação do alvo molecular das 2(quinolin-4-ilóxi) acetamidas como candidatos a fármacos para o tratamento da tuberculose - Subtil, Fernanda Teixeira (2017)
The high incidence of tuberculosis is a great concern worldwide. Different strategies are being developed by the World Health Organization to fight tuberculosis. Amongst the three pillars that are part of the End TB Strategy, we can highlight the intensive research and innovation pillar. In this extent, the development of new drugs for tuberculosis treatment is a field that is gaining importance. The 2(quinolin-4-yloxy) acetamides are molecules that showed promising bactericidal effects in Mycobacterium tuberculosis, which motivated us to continue studying to improve their mycobactericidal activity and also perform their chemical and biological characterization. In order to continue the 2(quinolin-4-yloxy) acetamides derivatives development, the target identification of these molecules is a keystone and is also the focus of this study. Initially, it was hypothesized that DNA gyrase was their molecular target due to the great chemical similarities between the 2(quinolin-4-yloxy) acetamides and the fluoroquinolones. Despite our results that the 2(quinolin-4-yloxy) acetamides have diminished effects in ofloxacin resistant clinical isolates, the results obtained with the gyrA point mutant and with DNA gyrase protein revealed that this enzyme is not the molecular target of these compounds. The new target identification strategy involved the selection of spontaneous mutants for our lead compound 12L, characterization of this mutant strain against other 2(quinolin-4-yloxy) acetamides derivates and whole genome sequencing. Whole genome sequencing data allowed the identification of a single mutation (T313A) in the QcrB protein, which is the B subunit of cytochrome bc1 complex. This mutation was confirmed by Sanger sequencing and molecular docking results confirmed the importance of this residue for proteindrug interaction. The cytochrome bc1 complex is involved in the electron transport of the bacilli’s respiratory chain, and therefore it appears to be an interesting target, especially to treat the latent form of the disease. We hope that this work contributes to the 2(quinolin-4-yloxy) acetamides development for tuberculosis treatment.